TATA KELOLA KOMUNIKASI DALAM PENGEMBANGAN EKOSISTEM MANGROVE SEBAGAI EKOWISATA EKONOMI KREATIF DAN KEARIFAN LOKAL KABUPATEN BENGKALIS - Nurjanah Nurjanah; Yasir Yasir; Nova Yohana; Hevi Susanti (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
Teluk Pambang Village has an attraction with the. Mangrove. .forest ecosystemmin the form of views of the physical environment of waters, rivers and expanses of mangrove vegetation, flora and fauna which are currently being managed as tourist destinations. The .purpose of the researchs is to reveal.. the management .of communication in the development of the village's creative economy. Through ddescriptive qualitativey .methods, the dataa was collected through observation, and interviews with the. mangrove ecotourism management team. The results show that integrated management through various communication resources in the context of effective communication can have an impact on improving the community's economy independently, through the process of planning, implementing, and controlling various elements of communication accordingg to the goals that have been set. The forms of. ccommunicationn in achievingg goals is adjustedt to the character of the local community, through various socialization, mentoring and counseling activities that have used information and technology media. Although the community is aware that tourism has the potential to independently improve the community's economy, it has not yet been implemented properly, there is still room for improvement in each region based on an integrated development approach.